Geo Inspiration – a collaborative site in Geographic content for High School (Research, Society and Development, 2020)
The growing number of information produced on the internet sometimes makes research difficult and the lack of an appropriate place as a reference for studies is necessary. This article reports the construction of an educational software with geography content that aims to provide a space for building knowledge and debates on the topics addressed in high school in a collaborative way among the members of the site. The objective is to concentrate a space that is able to offer activities for students and at the same time a place for the exchange of knowledge between teachers, aiming to implement a specific content platform. There are some software that present the features that our platform proposes, such as Socrative, a virtual space to propose classroom activities. What sets our platform apart from other tools found on the internet is the proposal to be collaborative among teachers, and to have a study space for high school students. The result of our platform, in the process of being built, is available for access and registration, and we expect the adhesion of teachers and wide dissemination of this topic so that this site is a reference for studies in Geography for High School.